Levantamento de inventário de emissões de gases de efeito estufa em obra da indústria da construção civil em Maringá - PR - MACIEL, Marco Aurélio Diniz (2016)
Climate change is recognized as one of the main barriers to sustainable development and many human activities such as transportation, industry, civil construction and agriculture are responsible for those changes. Nevertheless, the civil construction sector contributes to one third of global CO2 emissions, what makes it one of the main human activities that causes the most severe environmental impacts, especially due to the consumption of energy and natural resources. It is known that civil construction emissions are associated with the extraction of raw materials used in construction materials, the production processes of these materials, the energy expended during the construction site life cycle, its operation and maintenance, besides the waste disposal and the transportation of materials. To promote actions to reduce GHG emissions and contribute to climate change mitigation, the civil construction sector has to evaluate the source of emissions and calculate the amount of greenhouse gases emitted. This can be done through GHG emission inventories. The results obtained from the inventories can be then used to define actions that result in lower emissions. Therefore, quantifying and organizing GHG emissions data and to study the mitigation potential in this sector will contribute to solving the problem of global climate change and provide benefits such as lower air pollution, human health improvement, lower mortality rate, improvement of the social welfare, energy security. The objective of this study was to develop a GHG inventory from the construction of a commercial building in the city of Maringa / PR. To prepare this inventory the data were obtained from the descriptive memorial of the construction site and the construction site service sheet and used the tool "GHG Protocol", 2013 version 2014.0 and 2013.1.1. The inventory was recorded throughout the construction time, occurred in 2014, and the following activities were considered: the masonry services and fencing, roofing, waterproofing, lining coating, flooring, interior and exterior walls, painting and frames as described in descriptive memorial and the construction site service sheet. Based on the results found it was concluded that the total GHG emissions in the assessed construction site was 907.049,93 kg CO2 at a total construction area of 10,987 m². These data resulted in the issuance of 82,56 kgCO2 / m². The materials responsible for the higher greenhouse gases emissions were the tile floors (48%), the concrete and mortar (32.3%). The total GHG emissions due to transportation of the equipment were 55.002,54 kg CO2, equivalent to 6.06% of the total inventory emissions. Seeking for a greater environmental sustainability, it was estimated that a reforestation project with 7.068 units of natives trees is enough to compensate the emissions observed.